2013
DOI: 10.3892/or.2013.2504
|View full text |Cite
|
Sign up to set email alerts
|

Active extracts of black tea (Camellia Sinensis) induce apoptosis of PC-3 prostate cancer cells via mitochondrial dysfunction

Abstract: Cancer of the prostate gland is the most common invasive malignancy and the second leading cause of cancer-related death in human males. Many studies have shown that black tea reduces the risk of several types of cancer. We studied the effects of active extracts of black tea and the black tea polyphenols theaflavins (TFs), on the cellular proliferation and mitochondria of the human prostate cancer cell line PC-3. Our studies revealed that Yinghong black tea extracts (YBT), Assam black tea extracts (ABT) and TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…tested the potency of EGCG for the inhibition of cell proliferation in PC-3 prostate cancer cells and reported similar concentration values [7, 13, 2022] to ours. It is of great importance that EGCG had no effect on cell proliferation in the RWPE-1 non-tumorigenic prostate epithelial cell line.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…tested the potency of EGCG for the inhibition of cell proliferation in PC-3 prostate cancer cells and reported similar concentration values [7, 13, 2022] to ours. It is of great importance that EGCG had no effect on cell proliferation in the RWPE-1 non-tumorigenic prostate epithelial cell line.…”
Section: Resultssupporting
confidence: 75%
“…No work was done with TF on DU145 prostate cancer cells. However, as we stated in the introduction, TFs were used to limit proliferation in different prostate cancer cells in similar concentrations as those used in our experiments [13, 17, 22]. …”
Section: Resultsmentioning
confidence: 99%
“…The biological effects of polyphenols on metabolically active tissues affect insulin sensitivity, inflammation, lipid metabolism which could be triggered by activation of peroxisome proliferation activated receptors (PPARs) by polyphenols (Cho et al 2010). Recent studies (Sun et al 2013) on prostate cancer cells revealed that polyphenols rich tea extracts inhibited cell proliferation, induced apoptosis, and provide reduction of the mitochondrial membrane potential. Apart from polyphenols, saponins are glucosides found in vegetables and their non-sugar moiety has been reported to show anti oxidant property (Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have largely been directed toward the biological properties of GT, currently there are also evidence showing the health benefits of BT. In this sense, Bahorun et al (2012), Fatima and Rizvi (2015), Grassi, Draijer, Desideri, Mulder, and Ferri (2015), Pan et al (2013), Sun et al (2013) and Tang, Li, Liu, Huang, and Ho (2013) indicated the benefits of BT in the prevention of cancer and many inflammatory and metabolic diseases including cardiovascular diseases. Furthermore, the potential health benefits associated with tea consumption have been largely ascribed to the antioxidant capacity of its bioactive molecules (Khan & Mukhtar, 2007;Liu & Huang, 2014).…”
Section: Introductionmentioning
confidence: 99%